Strategic Litigation in a Time of Populism: Poland’s Experience - Adam Ploszka (German Law Journal)
For strategic litigation, the existence of independent judicial institutions is a prerequisite. In this Article, based on the case of Poland, I analyze what happens when some domestic judicial institutions are weakened and how this affects the ability of different stakeholders to engage in strategic litigation. I argue that strategic litigation was an important tool used by civil society and crucial for countering democratic backsliding in Poland in 2015–2023. In addition to traditional actors involved in strategic litigation in Poland, new ones have joined—such as the Human Rights Commissioner (the “Ombudsman”) or increased their involvement—such as corporate actors. Also, the prosecution office, controlled by the populist government, became active in litigation conducted by right-wing NGOs. Paradoxically, the rule of law crisis also resulted in the popularization of strategic litigation before the Court of Justice of the European Union and some domestic courts, which began to apply the Constitution directly.